Menampilkan Islam Rahmatan lil 'Alamin - Arifuddin Arifuddin (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This research aims to explore the meaning and relevance of Islam Rahmatan lil 'Alamin in the modern era, by focusing on three main pillars: justice, brotherhood, and balance. The research method used in this study is the literature review method. This method involves the analysis and synthesis of various sources of literature related to Islam Rahmatan Lil 'Alamin. Islam Rahmatan lil 'Alamin, which means